Crystallized glass, high-frequency substrate, and method for manufacturing crystallized glass

By using crystallized glass with Ba-Si-O components and fire treatment under low temperature conditions, the problem of large dielectric loss in high-frequency equipment is solved, and low-die loss and low-cost high-frequency substrate is achieved.

JP2025061344AActive Publication Date: 2025-04-10AGC INC
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2025005698
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2020-03-30
Filing Date
2025-01-15
Publication Date
2025-04-10
Estimated Expiration
2041-01-27

AI Technical Summary

Technical Problem

In the prior art, high-frequency equipment has a large dielectric loss, especially in the high-frequency range, and it is difficult to achieve a dielectric substrate with low dielectric loss.

Method used

The crystallized glass with Ba-Si-O as the main component is melted into glass by melting the original material of BaO and SiO2 into glass, and then heat treatment is performed between 600°C and 1000°C to achieve a low-temperature fire of the crystallized glass.

Benefits of technology

High-frequency substrate with low dielectric loss is realized, reducing production costs and improving material processability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025061344000001_ABST
    Figure 2025061344000001_ABST
Patent Text Reader

Abstract

To provide a material which can be manufactured inexpensively and has high degree of freedom of formation and which can be fired at low temperatures and has a small dielectric dissipation factor.SOLUTION: A crystallized glass of the invention is glass having a crystalline phase composed only of Ba-Si-O.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to crystallized glass, a high frequency substrate using crystallized glass, and a method for manufacturing the same. [Background technology]

[0002] In recent years, wireless transmission using microwave and millimeter wave bands has been attracting attention as a large-capacity transmission technology. However, as the signal frequency increases with the expansion of the frequency range used, there is a problem that the dielectric loss of high-frequency devices increases. Therefore, a dielectric substrate with low dielectric loss is required. The material of this dielectric substrate is selected from, for example, quartz, ceramics, glass, etc. Here, even if it is glass, crystallized glass obtained by crystallizing a part of glass has the advantage that it can be easily molded and manufactured at low cost compared to quartz and ceramics, and can reduce dielectric loss. An example of low-loss crystallized glass is indialite / cordialite crystallized glass as shown in Non-Patent Document 1. [Prior art documents] [Non-patent literature]

[0003] [Non-Patent Document 1] H. Ohsato, J S. Kim, A Y. Kim, C I. Cheon, K W. Chae, Millimeter Wave Dielectric Properties of Cordierite / Indialite Glass Ceramics, Jpn. J. Appl. Phys., 50 (2011) 09NF01 1 5. Summary of the Invention [Problem to be solved by the invention]

[0004] However, the crystallized glass disclosed in Non-Patent Document 1 requires a crystallization treatment at a high temperature exceeding 1200°C. In view of the above background, an object of the present invention is to provide a crystallized glass that can be fired at a low temperature. [Means for solving the problem]

[0005] The present invention provides a crystallized glass having a crystal phase consisting only of Ba-Si-O.

[0006] The present invention also provides a high frequency substrate using the above crystallized glass.

[0007] In the present invention, The present invention provides a method for producing crystallized glass having a crystal phase consisting only of Ba-Si-O, comprising melting and forming a raw material containing BaO and SiO2 to obtain amorphous glass, and then maintaining the amorphous glass at a processing temperature of 600°C or higher and lower than 1000°C to crystallize the glass. Effect of the Invention

[0008] According to the present invention, it is possible to obtain a crystallized glass that can be fired at a low temperature, and a high frequency substrate using the same. [Brief description of the drawings]

[0009] [Figure 1] FIG. 1 is a diagram showing the relationship between the total crystallinity of BaSi2O5 and Ba2Si4O10 and the dielectric tangent tan δ in an experimental example. [Diagram 2] FIG. 2 is a diagram showing the relationship between the crystallinity and the dielectric tangent tan δ of Li2Si2O5 in the composition H in the experimental example. [Diagram 3] FIG. 3 is a diagram showing the relationship between the sum of squares of the differences in the lattice constants of BaSi2O5 and Ba2Si4O10 and the dielectric tangent tan δ in the experimental example. [Figure 4] FIG. 4 is a graph showing the relationship between the product of the sum of the strain and the crystallinity in the {400}, {020}, and {002} planes of BaSi2O5 and Ba2Si4O10 of index 2 and the dielectric tangent tanδ of the crystallized glass. [Diagram 5]FIG. 5 shows the results of DSC measurements showing the crystallization onset temperature when X is changed from 0.2, 0.5, 1.0, 2.0, 3.0, to 5.0 in the XLi2O-(30-X)BaO-70SiO2 composition. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] <Glass-ceramics> First, the crystallized glass of the present invention will be described. The crystallized glass of the present invention is characterized by having a crystal phase consisting only of Ba-Si-O. The crystallized glass of the present invention can be produced by melting and molding an amorphous glass containing BaO and SiO2, and then using the amorphous glass block after annealing, heat treatment at a low temperature of less than 1000°C to precipitate crystals consisting only of Ba-Si-O.

[0011] Here, "crystallized glass" refers to glass in which crystals are precipitated. In the present application, "crystallized glass" refers to glass in which a diffraction peak indicating crystals is observed by powder X-ray diffraction (PXRD). Powder X-ray diffraction measurement is performed using CuKα radiation in the range of 2θ of 10° to 80° as described below, and when a diffraction peak appears, precipitated crystals can be identified by, for example, the three strongest radiation method.

[0012] In this specification, unless otherwise specified, the glass composition is expressed in mole percent based on oxides, and mole percent is simply expressed as "%." In addition, in this specification, "substantially free" means that the content is below the impurity level contained in raw materials, etc., that is, that it is not intentionally added. Specifically, it is, for example, less than 0.01%.

[0013] The crystalline phase consisting of only Ba-Si-O is, for example, BaSi2O5, Ba2Si4O 10 , BaSiO3, Ba2Si3O8, Ba5Si8O 21 , Ba3SiO 13 , and Ba3SiO 21and the like, preferably BaSi2O5 and Ba2Si4O 10 It contains at least one of the following.

[0014] Among the above crystal species, BaSi2O5 has a particularly small dielectric tangent in the high frequency range, and by including BaSi2O5, it is possible to realize a crystallized glass with a low dielectric tangent in the high frequency range. Note that the high frequency refers to a band of 1 GHz or more, and in this application, the dielectric tangent at 10 GHz or 28 GHz is specifically mentioned. Ba2Si4O 10 Ba2Si4O has a fast crystal growth rate and a low dielectric tangent at 10 GHz. 10 By containing , it is possible to achieve a crystallized glass with a low dielectric tangent and small dielectric loss by short-term heat treatment. The dielectric properties such as the dielectric tangent and relative dielectric constant are measured by the slip post dielectric resonance method (SPDR method).

[0015] More preferably, the crystalline phase consisting of only Ba-Si-O is BaSi2O5 or Ba2Si4O 10 By containing as the main phase or the second phase, the dielectric tangent at high frequencies can be particularly small.

[0016] In addition, the crystallized glass may contain a crystal phase other than the crystal phase consisting of only Ba-Si-O, as long as the dielectric tangent of the crystallized glass is not deteriorated. The crystal phase other than the crystal phase consisting of only Ba-Si-O is, for example, K2Ba7Si 16 O 40 , ZrO2, TiO2, SnO2, ZrTiO4, Li2(Si2O5), Li2(SiO3), LiAl(SiO3)2, SiO2, Ba(Al2Si2O8), etc.

[0017] Here, these crystal species are identified by PXRD. BaSi2O5 is a crystal that shows diffraction peaks at Bragg angles (2θ) of, for example, 17.5°±0.2°, 22.4°±0.2°, and 26.7°±0.2° using CuKα radiation, and Ba2Si4O 10is a crystal that exhibits diffraction peaks at Bragg angles (2θ) of, for example, 18.9°±0.2°, 22.3°±0.2°, and 25.2°±0.2° using CuKα radiation.

[0018] Furthermore, in order to know the crystal structure more accurately, it is preferable to perform Rietveld analysis. Rietveld analysis enables quantitative analysis of the crystalline phase and the amorphous phase, and structural analysis of the crystalline phase. The Rietveld method is described in "Crystal Analysis Handbook" edited by the Editorial Committee of the Crystallographic Society of Japan (Kyoritsu Shuppan, 1999, pp. 492-499).

[0019] (Crystallization degree) As a result of the above analysis, it was found that the high frequency dielectric properties of the crystallized glass of the present invention are related to the crystallization degree, which indicates the content ratio of the crystal phase. The crystallization degree is defined as the ratio of a specific crystal to the entire crystallized glass. In other words, the crystallization degree of BaSi2O5 means the ratio of BaSi2O5 crystals to the entire crystallized glass. The crystallization degree of BaSi2O5 and Ba2Si4O 10 The sum of the crystallinity of BaSi2O5 and Ba2Si4O is preferably 15 wt% or more. More preferably, it is 17 wt% or more, even more preferably, it is 18 wt% or more, even more preferably, it is 19 wt% or more, and even more preferably, it is 20 wt% or more. 10 When the total crystallinity of the above is within the above range, crystals can be sufficiently precipitated, the dielectric tangent can be small, and the dielectric loss can be suppressed, which is preferable.

[0020] On the other hand, the crystallinity of BaSi2O5 and Ba2Si4O 10 The sum of the crystallinity of the above is preferably 50 wt % or less based on the total weight of the crystallized glass, which makes it possible to suppress an increase in the dielectric tangent caused by the grain boundaries of the precipitated crystals and to make the dielectric tangent tan δ at 10 GHz 0.0030 or less.

[0021] Crystallinity of BaSi2O5 and Ba2Si4O 10The sum of the crystallinity of BaSi2O5 and Ba2Si4O is more preferably 45 wt% or less, even more preferably 40 wt% or less, even more preferably 35 wt% or less, and even more preferably 31 wt% or less. 10 When the total crystallinity is within the above range, the proportion of grain boundaries, which is one of the factors that increases the dielectric tangent, can be reduced, making it easier to make the dielectric tangent tan δ at 10 GHz 0.0010 or less. Specifically, the crystallinity of BaSi2O5 and Ba2Si4O 10 The preferred range of the total crystallinity is 15 wt % or more and 50 wt % or less.

[0022] Furthermore, the crystal phase may contain Li-based crystals. When the crystallized glass contains Li in the matrix composition, it has the advantage of lowering the crystallization temperature and increasing the crystallization rate. On the other hand, when the Li content in the matrix composition increases, Li-based crystals may precipitate in the crystallized glass's crystallized phase, and the Li-based crystals may increase the dielectric tangent of the crystallized glass, so it is preferable that the content is small. When the crystallization degree of the Li-based crystals is preferably 20wt% or less with respect to the total weight of the crystallized glass, the dielectric tangent tanδ at 10GHz is easily made 0.0030 or less. When the crystallization degree of the Li-based crystals is more preferably 15wt% or less, the dielectric tangent tanδ at 10GHz is easily made 0.0020 or less. When the crystallization degree of the Li-based crystals is more preferably 10wt% or less, the dielectric tangent tanδ is easily made 0.0010 or less. The crystallization degree of the Li-based crystals is even more preferably 5wt% or less, and it is most preferable that the Li-based crystals are not contained.

[0023] More specifically, it has been found that the high-frequency dielectric properties of the crystallized glass of the present invention are related to the degree of crystallization and the distortion of the crystals. By precipitating a large amount of crystals with less distortion, the dielectric loss at high frequencies can be suppressed. Therefore, the following two indexes can be used as indexes reflecting the above characteristics. By satisfying at least one of the following two indexes, the dielectric tangent tan δ at 10 GHz can be made 0.0030 or less, and the dielectric loss at high frequencies can be suppressed, which is preferable.

[0024] (Index 1) The sum of squares of the differences in lattice constants, expressed by the following formula, is 0.050 or less. (Sum of squares of lattice constant differences) = (A BS2 -A' BS2 ) 2 +(B BS2 -B' BS2 ) 2 +(C BS2 -C' BS2 ) 2 +(A B2S4 -A' B2S4 ) 2 +(B B2S4 -B' B2S4 ) 2 +(C B2S4 -C' B2S4 ) 2

[0025] Here, the lattice constants of the a, b, and c axes of BaSi2O5 measured in the crystalline phase are A BS2 , B BS2 , C BS2 and Ba2Si4O 10 The lattice constants of a, b, and c axes are A B2S4 , B B2S4 , C B2S4 The lattice constant of BaSi2O5 in the ideal crystalline state described in ICSD Collection Code:15486 is A' BS2 , B' BS2 , C' BS2 and Ba2Si4O in the ideal crystal state described in ICSD Collection Code:9339. 10 The lattice constant of A' B2S4 , B' B2S4 , C' B2S4 In this specification, the lattice constant is C BS2 >A BS2 >B BS2 , C' BS2 >A' BS2 >B' BS2 , A B2S4 >C B2S4 >B B2S4 , A' B2S4 >C' B2S4 >B'B2S4 Each crystal axis is defined so as to satisfy the following:

[0026] (Index 2) The sum of the products of the crystallinity of BaSi2O5 and the strains on the {002}, {020}, and {400} planes of BaSi2O5, and the Ba2Si4O 10 Crystallinity and Ba2Si4O 10 The sum of the products of distortions in the {002}, {020} and {400} planes is 0.030 or less, where the {002}, {020} and {400} planes are Miller index notations representing crystal lattice planes.

[0027] Regarding (Index 1) In the index 1, as described above, it is preferable that the sum of squares of the differences in the lattice constants expressed by the following formula is 0.050 or less. (Sum of squares of lattice constant differences) = (A BS2 -A' BS2 ) 2 +(B BS2 -B' BS2 ) 2 +(C BS2 -C' BS2 ) 2 +(A B2S4 -A' B2S4 ) 2 +(B B2S4 -B' B2S4 ) 2 +(C B2S4 -C' B2S4 ) 2 Here, as a result of the Rietveld analysis mentioned above, the lattice constant of BaSi2O5 in the crystalline phase is A BS2 , B BS2 , C BS2 and Ba2Si4O 10 The lattice constant of A B2S4 , B B2S4 , C B2S4 This is expressed as: On the other hand, the lattice constant of BaSi2O5 in an ideal crystal state is A' BS2 , B' BS2 , C' BS2 and Ba2Si4O 10 Lattice constant A' B2S4, B' B2S4 , C' B2S4 Let A' be BS2 , B' BS2 , C' BS2 The value of is the value described in ICSD Collection Code:15486, A' B2S4 , B' B2S4 , C' B2S4 The value of shall be that described in ICSD Collection Code:9339.

[0028] Hereinafter, the above value may be simply referred to as "the sum of squares of the differences in lattice constants."

[0029] In other words, the sum of squares of the differences in lattice constants represents the deviation of the lattice constants of the crystals in the crystallized glass of the present invention from the lattice constants of ideal crystals, and is a parameter that represents the degree of distortion of the crystals.

[0030] The sum of squares of the difference of lattice constants is 0.050 or less, so that the crystallized glass contains many crystals with little distortion, and therefore the dielectric loss tangent tanδ at 10GHz is easily suppressed to 0.0030 or less. More preferably, the sum of squares of the difference of lattice constants is 0.045 or less, even more preferably 0.040 or less, even more preferably 0.035 or less, particularly preferably 0.030 or less, and most preferably 0.025 or less, so that the dielectric loss tangent at 10GHz is easily suppressed to be smaller.

[0031] Indicator 1, the crystallinity of BaSi2O5 and Ba2Si4O 10 It is more preferable that the total value of the crystallinity of BaSi2O5 is 15% or more and 50% or less in weight percent, and the sum of the squares of the differences in the lattice constants is 0.050 or less. 10 It is more preferable that the total crystallinity of the Li-based crystals is 15 wt% or more and 50 wt% or less, the crystallinity of the Li-based crystals is 20 wt% or less, and the sum of squares of the differences in lattice constants is 0.050 or less. In particular, the crystallinity of BaSi2O5 and Ba2Si4O 10When the total crystallinity of the Li-based crystals is 15 wt% or more and 31 wt% or less, the crystallinity of the Li-based crystals is 20 wt% or less, and the sum of the squares of the differences in the lattice constants is 0.025 or less, it is easy to suppress the dielectric tangent tanδ to 0.0010 or less, which is preferable.

[0032] Regarding indicator 2, As described above, the index 2 is the sum of the crystallinity of BaSi2O5 and the product of the strains on the {400}, {020} and {002} planes of BaSi2O5, and Ba2Si4O 10 Crystallinity and Ba2Si4O 10 It is preferable that the sum of the products of the strains in the {400}, {020} and {002} planes (hereinafter sometimes referred to as "crystallinity x strain sum") is 0.030 or less.

[0033] Crystallinity of BaSi2O5 and Ba2Si4O 10 The crystallinity and distortions in the {400}, {020} and {002} planes of BaSi2O5 are determined by the above-mentioned PXRD and Rietveld analysis. Here, the distortions in the {400}, {020} and {002} planes of BaSi2O5 are values ​​determined by Rietveld analysis of peaks appearing in the vicinity of 47.1-47.4°, 38.4-38.8° and 12.9-13.1° in PXRD, respectively. Ba2Si4O 10 The distortions in the {400}, {020}, and {002} planes are values ​​determined by Rietveld analysis of peaks appearing in the vicinity of 15.3 to 15.4°, 38.3 to 38.5°, and 13.0 to 13.2° in PXRD.

[0034] In index 2, when the sum of the degree of crystallinity and the strain is 0.030 or less, the total amount of strain in the crystal can be reduced, and the dielectric tangent tan δ at 10 GHz tends to be 0.0030 or less. The sum of the degree of crystallinity and the strain is preferably 0.025 or less, and more preferably 0.020 or less. Even more preferably, when the sum is 0.019 or less, the dielectric tangent tan δ at 10 GHz tends to be 0.0010 or less. On the other hand, the sum of the degree of crystallinity and the strain is preferably 0.001 or more.

[0035] Indicator 2, the crystallinity of BaSi2O5 and Ba2Si4O 10 It is more preferable that the total crystallinity value of the above is 15 wt% or more and 50 wt% or less, the crystallinity of the Li-based crystal is 20 wt% or less, and the sum of the crystallinity x strain is 0.030 or less.

[0036] The dielectric properties of the crystallized glass can be significantly improved by satisfying either the above condition of index 1 or 2. The crystallized glass may also satisfy both conditions simultaneously.

[0037] (Crystallite size) The dielectric properties of the crystallized glass of the present invention are also related to the crystallite size. If the crystallite size is large, the ratio of the interface between the glass and the crystal and the grain boundary can be reduced, and the dielectric loss tangent can be suppressed. The dielectric properties of the crystallized glass of the present invention are particularly related to the crystallite size of Ba2Si4O 10 It shows a good correlation with the average crystallite size of the crystalline phase. Ba2Si4O 10 The average crystallite size is preferably 20 nm or more, more preferably 32 nm or more, so that the dielectric tangent tan δ at 10 GHz tends to be 0.0010 or less. More preferably, it is 40 nm or more, even more preferably 45 nm or more, and particularly preferably 50 nm or more. When the average crystallite size is preferably 100 nm or less, it is possible to suppress the phenomenon in which crystal grains are unevenly distributed and the characteristics vary, and the phenomenon in which the strength is locally reduced.

[0038] (Mother composition of glass-ceramics) In addition, the matrix composition of the crystallized glass of the present invention is the same as the composition of the amorphous glass before crystallization in the manufacturing method described below. Here, the matrix composition of the crystallized glass in this application refers to the composition of the total of the crystalline part and the amorphous part of the crystallized glass. In addition, the matrix composition of the crystallized glass is obtained by performing heat treatment on the crystallized glass at a temperature above its melting point, and analyzing the vitrified product. Examples of the analysis method include fluorescent X-ray analysis and laser ablation ICP mass spectrometry.

[0039] (Orientation of precipitated crystals) In the process of molding or heat treatment, the precipitated crystals may be oriented by applying an electric field, a magnetic field, or a temperature field, or by applying stress. For certain crystal species, crystals with orientation on the surface of the amorphous glass may be precipitated by heat treatment in a uniform field. However, the means for imparting orientation are not limited to these means.

[0040] By giving orientation to the precipitated crystals, the anisotropy of glass properties, such as dielectric properties and optical properties, can be given to the crystallized glass. The anisotropy of glass properties here refers to, for example, the property that when the dielectric constant of a crystallized glass plate is measured, the dielectric constant in the direction perpendicular to the main surface with the largest area of ​​the crystallized glass plate is different from the dielectric constant in the direction parallel to the main surface. However, the physical properties having anisotropy are not limited to the above physical properties.

[0041] The crystal orientation referred to here is the property that the crystals precipitated in the crystallized glass are aligned in a specific direction compared to a random state. When the X-ray diffraction spectrum of the crystallized glass is obtained using the method described below, the crystal orientation can be confirmed from the difference in the X-ray diffraction spectrum obtained from the block of the crystallized glass before polishing, the plate after polishing, and the powder obtained by crushing the polished glass.

[0042] (High frequency substrate) The above-mentioned crystallized glass can be used for high frequency substrates because it can reduce the dielectric loss tangent at high frequency. The high frequency substrate using the crystallized glass of the present invention preferably has a dielectric loss tangent at 10 GHz of 0.0030 or less, more preferably 0.0020 or less, even more preferably 0.0010 or less, even more preferably 0.0008 or less, and particularly preferably 0.0005 or less. If the dielectric loss tangent at 10 GHz satisfies the above, it can be suitably used in a frequency band higher than 10 GHz, such as 28 GHz or 79 GHz. The dielectric loss tangent at 28 GHz is preferably 0.0080 or less, more preferably 0.0060 or less, even more preferably 0.0040 or less, even more preferably 0.0020 or less, and particularly preferably 0.0010 or less. The dielectric loss tangent at 79 GHz is preferably 0.0100 or less, more preferably 0.0080 or less, even more preferably 0.0060 or less, still more preferably 0.0040 or less, particularly preferably 0.0030 or less, and most preferably 0.0020 or less.

[0043] As will be described later in the description of the production method, the crystallized glass of the present invention has excellent moldability and the crystallization treatment temperature can be set to less than 1000° C., so that it can be produced at low cost.

[0044] Furthermore, in the high frequency substrate using the crystallized glass of the present invention, the relative dielectric constant at 10 GHz is preferably 6.0 or more from the viewpoint of miniaturization of high frequency components using the high frequency substrate. The relative dielectric constant at 10 GHz is more preferably 6.3 or more, and even more preferably 6.5 or more. On the other hand, in order to be able to be used stably in a wide frequency band, the relative dielectric constant is preferably 8.0 or less, more preferably 7.8 or less, and even more preferably 7.5 or less. The dielectric properties such as the dielectric loss tangent and the relative dielectric constant are measured by the slip post dielectric resonance method (SPDR method).

[0045] Furthermore, the crystallized glass of the present invention preferably has an average thermal expansion coefficient of 15 ppm / K or less measured at 50 to 350 ° C. in order to suppress the occurrence of cracks when holes are drilled by laser irradiation. The average thermal expansion coefficient is more preferably 14.5 ppm / K or less, and even more preferably 14 ppm / K or less. On the other hand, the average thermal expansion coefficient is preferably 10 ppm / K or more, more preferably 11 ppm / K or more, and even more preferably 12 ppm / K or more. When the average thermal expansion coefficient is within the above range, the mismatch of the thermal expansion coefficient with silver or copper wiring is suppressed when the crystallized glass of the present invention is used as a high-frequency substrate, and the adhesion of the wiring can be improved.

[0046] Furthermore, in order to efficiently dissipate heat generated when used as a high frequency substrate, the crystallized glass of the present invention preferably has a thermal conductivity λ of 2.0 W / m·K or more at room temperature. The thermal conductivity λ is more preferably 2.3 W / m·K or more, even more preferably 2.5 W / m·K or more, still more preferably 2.8 W / m·K or more, and particularly preferably 3.0 W / m·K or more. The thermal conductivity can be measured using the method described in JIS. R. 1611.:2010.

[0047] A high frequency substrate generally has two main surfaces facing each other. When used as a high frequency substrate in the present invention, the area of ​​the main surfaces is 75 cm2. 2 More preferably, 100 cm 2 More than 150cm, more preferably 2 More preferably, 300 cm 2 More than 700 cm, especially preferred 2 The shape of the high frequency substrate can be freely designed according to the application as long as it has the above area.

[0048] The thickness of the high frequency substrate of the present invention is preferably 1 mm or less, more preferably 0.8 mm or less, and even more preferably 0.7 mm or less. When the thickness is within the above range, the entire substrate can be made thin when the substrates are laminated to form a circuit. On the other hand, when the thickness is preferably 0.05 mm or more, more preferably 0.2 mm or more, strength can be ensured.

[0049] Furthermore, the high frequency substrate of the present invention may have holes with openings on at least one of the main surfaces. The holes may be through holes communicating with the other main surface, or may be non-through voids. These holes may be filled with a conductor or a conductor film may be formed on the hole walls, so that the substrate can be used as a circuit.

[0050] The diameter of the pores is, for example, 200 μm or less, preferably 100 μm or less, while the diameter of the pores is preferably 1 μm or more.

[0051] <Method of manufacturing crystallized glass> Next, a method for producing crystallized glass having a crystal phase consisting only of Ba-Si-O according to the present invention will be described. A method for producing plate-shaped glass will be described below, but the shape of the glass can be appropriately adjusted depending on the purpose. The production method of the present invention is as follows: A raw material containing BaO and SiO2 is melted and molded to obtain amorphous glass (hereinafter referred to as the "amorphous glass molding process"); The amorphous glass is crystallized by maintaining the amorphous glass at a treatment temperature of 600° C. or more and less than 1000° C. (hereinafter referred to as the "crystallization step"); Each step will be described in detail below.

[0052] (Amorphous glass forming process) In this process, raw materials containing BaO and SiO2 are melted and formed into amorphous glass. The melt forming method is not particularly limited, but for example, glass raw materials prepared to obtain the glass composition shown below are placed in a platinum crucible and put into an electric furnace at 1300°C to 1700°C to melt, degas, and homogenize. The obtained molten glass is poured into a metal mold (e.g., a SUS surface plate) at room temperature, and is kept at the glass transition temperature for about 3 hours, and then cooled to room temperature to obtain a glass block.

[0053] In this way, amorphous glass can be formed into a desired shape from a molten state, and therefore has advantages over processes such as ceramics, which are formed from a powder or slurry and then fired, or synthetic quartz, which are formed from an ingot and then cut into a desired shape, in that it is easier to form and produce large areas; and also in view of the heat treatment in the crystallization process described below, amorphous glass can be produced at low cost.

[0054] The composition of the amorphous glass is described below. The composition is not particularly limited as long as it contains BaO and SiO2, but examples thereof include the following compositions expressed in mole percent based on oxides. Here, 0% includes cases where the composition is not contained.

[0055] (Composition 1) SiO2: 68-78% Al2O3: 0~5% BaO: 24-35% Li2O: 0~6% Na2O: 0-3% K2O: 0~3% ZrO2: 0-4% TiO2: 0-4% Contains (Li2O+Na2O+K2O): 0~6% is satisfied.

[0056] Each component will be described in detail below.

[0057] SiO2 is an essential component that forms the network structure of glass. The precipitated crystals BaSi2O5 and Ba2Si4O 10It is also a component of the present amorphous glass. When the content of SiO2 in the present amorphous glass is preferably 68% or more, the chemical durability of the amorphous glass can be increased and the desired crystals can be precipitated. The content of SiO2 is more preferably 68.5% or more, even more preferably 69% or more, and even more preferably 69.5% or more. On the other hand, when the content of SiO2 in the amorphous glass is 78% or less, the viscosity of the amorphous glass during melting is reduced, making it easier to melt and allowing the desired crystals to be precipitated. The content of SiO2 is preferably 75% or less, more preferably 74% or less, even more preferably 73% or less, and even more preferably 72% or less.

[0058] BaO is a constituent of precipitated crystals and is an essential component. When the content of BaO in the amorphous glass is preferably 24% or more, the viscosity of the amorphous glass during melting is reduced, making it easier to melt and allowing the desired crystals to precipitate. The content of BaO is more preferably 25% or more, even more preferably 26% or more, and most preferably 27% or more. On the other hand, when the content of BaO is preferably 35% or less, the chemical durability of the amorphous glass is improved and the desired crystals can be allowed to precipitate. The content of BaO is more preferably 33% or less, even more preferably 32% or less, even more preferably 31% or less, and particularly preferably 30% or less.

[0059] Li2O is an optional component and may be contained, lowering the temperature at which crystals consisting of only Ba-Si-O are generated and increasing the crystal growth rate. The content of Li2O is preferably more than 0%, more preferably 0.01% or more, even more preferably 0.05% or more, even more preferably 0.1% or more, particularly preferably 0.2% or more, especially particularly preferably 0.5% or more, and most preferably 1% or more. On the other hand, when the content of Li2O is preferably 6% or less, it is possible to suppress an increase in the dielectric tangent of the crystallized glass, phase separation of the amorphous glass that affects the crystallization behavior, and precipitation of crystals containing Li. The content of Li2O is more preferably 5% or less, and even more preferably 4% or less.

[0060] Al2O3 is an optional component and may be contained, which contributes to suppression of crystallization during pouring of amorphous glass and improvement of chemical durability of amorphous glass. When Al2O3 is contained, the content of Al2O3 is preferably 0.01% or more, more preferably 0.05% or more, and even more preferably 0.1% or more. On the other hand, by containing Al2O3 in a range not exceeding 5%, it is possible to suppress an increase in the dielectric tangent of the crystallized glass. The content of Al2O3 is more preferably 3% or less, even more preferably 2% or less, even more preferably 1% or less, particularly preferably 0.9% or less, especially more preferably 0.8% or less, especially especially preferably 0.7% or less, and most preferably 0.5% or less.

[0061] Na2O is an optional component, and like Li2O, it lowers the temperature at which crystals consisting of only Ba-Si-O are generated and contributes to an increase in the crystal growth rate. When Na2O is contained, the content of Na2O is preferably 0.01% or more, more preferably 0.05% or more, and even more preferably 0.1% or more. On the other hand, by containing Na2O in a range that preferably does not exceed 3%, it is possible to suppress an increase in the dielectric tangent of the amorphous part of the crystallized glass. The content of Na2O is more preferably 2% or less, even more preferably 0.9% or less, even more preferably 0.8% or less, particularly preferably 0.7% or less, and most preferably 0.5% or less.

[0062] K2O is an optional component, and like Li2O, it lowers the temperature at which crystals consisting only of Ba-Si-O form and contributes to increasing the crystal growth rate. Furthermore, the inclusion of K2O results in the formation of K2Ba7Si with a low dielectric tangent. 16 O 40precipitates, and the dielectric loss tangent can be reduced. When K2O is contained, the content of K2O is preferably 0.01% or more, more preferably 0.1% or more, even more preferably 0.5% or more, and particularly preferably 1% or more. On the other hand, by containing K2O in a range not exceeding 3%, it is possible to suppress an increase in the dielectric loss tangent of the amorphous part of the crystallized glass. The content of K2O is more preferably 2% or less, and even more preferably 1% or less.

[0063] Li2O, Na2O and K2O are optional components, and the total content of these (Li2O+Na2O+K2O) is preferably 0-6%, but since the inclusion of these components lowers the crystallization onset temperature, (Li2O+Na2O+K2O) is more preferably more than 0%. (Li2O+Na2O+K2O) is more preferably 0.2% or more, even more preferably 0.5% or more, and particularly preferably 1% or more. On the other hand, if the total content of Li2O, Na2O and K2O is 6% or less, the increase in the dielectric tangent of the amorphous part of the crystallized glass can be suppressed. (Li2O+Na2O+K2O) is more preferably 5.5% or less, even more preferably 5% or less, particularly preferably 4% or less, and most preferably 3% or less.

[0064] ZrO2 is an optional component that constitutes crystal nuclei during crystallization treatment and may be contained. The content of ZrO2 is preferably more than 0%, more preferably 0.01% or more, even more preferably 0.1% or more, and even more preferably 0.5% or more. On the other hand, by containing ZrO2 in a range that does not exceed 4%, it is possible to suppress an increase in the dielectric tangent. The content of ZrO2 is more preferably 3% or less, and even more preferably 2% or less.

[0065] TiO2 is an optional component, and may be contained as a component that constitutes crystal nuclei during crystallization treatment. The content of TiO2 is preferably more than 0%, more preferably 0.01% or more, even more preferably 0.1% or more, and even more preferably 0.5% or more. On the other hand, TiO2 is preferably contained in a range not exceeding 4%, so that an increase in the dielectric tangent can be suppressed. The content of TiO2 is more preferably 3% or less, and even more preferably 2% or less.

[0066] The total content of ZrO2 and TiO2 is preferably more than 0%, more preferably 0.5% or more, and even more preferably 1% or more. On the other hand, the total content of ZrO2 and TiO2 is preferably 5% or less, more preferably 3% or less, and even more preferably 2% or less.

[0067] P2O5 is not essential, but may be contained since it has the effect of promoting phase separation of glass and promoting crystallization. When P2O5 is contained, the content is preferably 0.01% or more, more preferably 0.1% or more, and even more preferably 0.2% or more. On the other hand, if the content of P2O5 is too high, surface crystallization occurs during crystallization treatment, and the crystallized glass may break during processing. The content of P2O5 is preferably 1% or less, more preferably 0.8% or less, even more preferably 0.6% or less, and particularly preferably 0.5% or less.

[0068] Other components can be included as long as they do not impair performance. Examples of other components include B2O3, MgO, CaO, SrO, ZnO, SnO2, CeO, Fe2O3, Rb2O, and Y2O. 3、 Examples of such metal ions include SO3, Cl, F, Ag2O, WO3, MnO2, CoO, Sb2O3, Au2O3, and Cr2O3, and may be metal ions or oxides. The content of these metal ions or oxides is preferably 5% or less, more preferably 3% or less, even more preferably 2% or less, particularly preferably 1% or less, and even more preferably 0.5% or less.

[0069] (Composition 2) The composition of the crystallized glass of the present invention may have a composition α that is specified by the following test method. It is preferable that the crystallized glass having the composition α has a linear relationship between the sum of squares of the difference of the lattice constants that is obtained by the following test method and the dielectric loss tangent at 10 GHz.

[0070] Test Method: (i) A plurality of amorphous glasses each having a composition α are prepared, and a plurality of samples are produced by changing the crystallization conditions. (ii) The dielectric loss tangent of each of the samples is measured at 10 GHz. (iii) For each sample, the lattice constant A of BaSi2O5 in the crystalline phase BS2 , B BS2 , C BS2 and Ba2Si4O in the crystalline phase. 10 Lattice constant A B2S4 , B B2S4 , C B2S4 is measured using Rietveld analysis. (iv) The sum of squares of the differences in lattice constants for each sample is calculated using the following formula: The lattice constant of BaSi2O5 in the ideal crystal state, as described in ICSD Collection Code:15486, is A' BS2 , B' BS2 , C' BS2 and Ba2Si4O in the ideal crystal state described in ICSD Collection Code:9339. 10 The lattice constant of A' B2S4 , B' B2S4 , C' B2S4 Then, (Sum of squares of lattice constant differences) = (A BS2 -A' BS2 ) 2 +(B BS2 -B' BS2 ) 2 +(C BS2 -C' BS2 ) 2 +(A B2S4 -A' B2S4 ) 2 +(B B2S4 -B' B2S4 ) 2+(C B2S4 -C' B2S4 ) 2 (v) The correlation between the sum of squares of the differences in the lattice constants of the multiple samples and the dielectric loss tangents at 10 GHz of the multiple samples is calculated.

[0071] In addition, the linear relationship between the sum of squares of the differences in the lattice constants of each sample and the dielectric loss tangent at 10 GHz is expressed as the correlation coefficient R 2 This refers to a value of 0.85 or higher.

[0072] Since the sum of the squares of the differences in the lattice constants represents the degree of distortion of the crystal phase, when the sum of the squares of the differences in the lattice constants and the dielectric loss tangent at 10 GHz are in a linear relationship, the dielectric loss tangent at 10 GHz is BaSi2O5 and Ba2Si4O 10 The strain rate of the crystal phase of the glass-ceramic increases linearly with the increase in the degree of strain of the crystal phase. 10 Therefore, by selecting a composition α such that the sum of the squares of the lattice constant differences and the dielectric loss tangent at 10 GHz are in a linear relationship, BaSi2O5 and Ba2Si4O 10 can be precipitated predominantly.

[0073] That is, when the composition α is used, when the sum of squares of the differences in lattice constants is X and the dielectric tangent at 10 GHz is Y, it is preferable that the following relationship is satisfied using an arbitrary slope a and intercept b. Y=aX+b and a>0 and b<0.0030

[0074] The intercept b is preferably b<0.0030. The intercept b is the value of the dielectric tangent at 10 GHz that can be taken when the degree of distortion of the crystal phase is 0, and by selecting a composition α that satisfies at least b<0.0030, the distortion of the crystal phase can be suppressed by optimizing the crystallization process, and the dielectric tangent tanδ at 10 GHz can be easily made 0.0030 or less. More preferably, b≦0.0025, even more preferably b≦0.0020, even more preferably b≦0.0015, particularly preferably b≦0.0010, and most preferably b≦0.0008.

[0075] In general, a>0. Preferably a<0.060, more preferably a<0.050, and even more preferably a<0.040, the composition is such that the dielectric tangent is unlikely to increase with increasing strain, and the manufacturing conditions are easy to adjust.

[0076] The amorphous glass used in the production of the crystallized glass of the present invention preferably has composition 1 or composition 2 as described above.

[0077] (crystallization process) Next, the amorphous glass obtained in the amorphous glass forming step is heated at a temperature between 600°C and 1000°C to precipitate crystals consisting of only Ba-Si-O, thereby making it into crystallized glass. When the treatment temperature is 600°C or higher, crystallization proceeds. The treatment temperature is more preferably 630°C or higher, even more preferably 660°C or higher, even more preferably 690°C or higher, and particularly preferably 710°C or higher. When the treatment temperature is within the above range, crystallization proceeds sufficiently, the crystallization rate is increased, the distortion of the precipitated crystals is suppressed, and the crystallite size can be increased, which is preferable.

[0078] On the other hand, the treatment temperature is preferably 980°C or less, more preferably 950°C or less, even more preferably 900°C or less, even more preferably 870°C or less, and particularly preferably 850°C or less. When the treatment temperature is within the above range, crystals consisting of only Ba-Si-O can be made the main phase, and localized precipitation of crystals can be prevented. In addition, the energy and cost required for the heat treatment can be reduced compared to crystallized glass having cordierite and indialite as the main phase.

[0079] More specifically, the treatment temperature is preferably adjusted depending on the glass material. The temperature is preferably equal to or higher than the glass transition point Tg calculated when the amorphous glass is measured by a differential scanning calorimeter (DSC) according to the following procedure, because the rate of crystal nucleation and crystal growth is fast. The measurement of the crystallization temperature by DSC in this application is carried out as follows.

[0080] (Crystallization temperature by DSC) The crushed amorphous glass powder is measured by a differential scanning calorimeter (DSC), and the sample is heat-treated at the obtained exothermic peak temperature and PXRD measurement is performed, and the temperature at which crystallization is confirmed is determined as the crystallization temperature. During DSC measurement, the particle size of the amorphous glass powder is 106 to 180 μm, and the measurement is performed from room temperature to 1200 °C at a heating rate of 10 °C / min.

[0081] The holding time at the above treatment temperature is preferably 0.5 hours or more, more preferably 1 hour or more, more preferably 3 hours or more, and particularly preferably 6 hours or more. When the holding time is within the above range, crystallization proceeds sufficiently. On the other hand, the heating time is preferably 48 hours or less, more preferably 40 hours or less, and particularly preferably 30 hours or less, since a long heat treatment increases the cost of the heat treatment.

[0082] While the amorphous glass is held at the above treatment temperature, the treatment temperature may be constant as long as it is within the above range, or may be raised or lowered within the above range. For example, the temperature may be raised from room temperature to the first treatment temperature and held for a certain period of time, and then slowly cooled to room temperature. Alternatively, a two-stage heat treatment may be selected in which the temperature is raised from room temperature to the first treatment temperature and held for a certain period of time, and then subsequently held at a second treatment temperature higher than the first treatment temperature for a certain period of time, and then slowly cooled to room temperature. A two-stage heat treatment is preferable because the crystallite size can be uniformly controlled.

[0083] In the case of a two-stage heat treatment, the first treatment temperature is preferably in a temperature range where the crystal nucleation rate is high in the glass composition, and the second treatment temperature is preferably in a temperature range where the crystal growth rate is high in the glass composition. The temperature where the crystal nucleation rate is high corresponds to a temperature between the glass transition temperature Tg and the crystallization onset temperature Tx measured by DSC, and the temperature where the crystal growth rate is high refers to a temperature above the crystallization onset temperature Tx measured by DSC.

[0084] The crystallization glass contains alkali metals, Li2O, Na2O, and K2O, which reduces the crystallization start temperature (Tx), and allows crystallization at a lower temperature. For example, Figure 5 shows the results of DSC measurements when the composition of XLi2O-(30-X)BaO-70SiO2 is changed to X=0.2, 0.5, 1.0, 2.0, 3.0, and 5.0. The peaks indicated by the arrows in Figure 5 indicate the peak temperatures of crystallization. From the results in Figure 5, it can be seen that the crystallization start temperature (Tx) decreases as the amount of Li2O increases. In the DSC measurements in Figure 5, the particle size of the crystallization glass was 106 to 180 μm, and the heating rate was set to 10 °C / min.

[0085] The heating rate is not particularly limited, but is preferably 10° C. / min or less to prevent cracks caused by a mismatch in the expansion coefficients of the amorphous phase and the crystalline phase during heating. On the other hand, the heating rate is generally 5° C. / min or more.

[0086] The cooling rate is not particularly limited, but is preferably 10°C / min or less, more preferably 5°C / min or less, and even more preferably 1°C / min or less, so that warping of the crystallized glass and cracking due to mismatch in the expansion coefficient between the amorphous phase and the crystalline phase during cooling can be suppressed. On the other hand, the cooling rate is generally 0.5°C / min or more.

[0087] Through the above steps, crystals consisting only of Ba-Si-O are precipitated in the amorphous glass, and the above-mentioned crystallized glass can be produced.

[0088] (Manufacturing method of high frequency substrate) A high frequency substrate may be manufactured from the above crystallized glass. In this case, the crystallized glass is preferably formed into a plate shape having main surfaces facing each other.

[0089] The method may further include a step of forming holes in the high frequency substrate, the hole being preferably formed by a laser.

[0090] The type of laser is not particularly limited, but examples include CO2 laser, He-Ne laser, Ar ion laser, excimer XeF laser, Er:YAG laser, Nd:YAG laser, second and third high frequencies of Nd:YAG laser, ruby ​​laser, fiber laser, etc. The laser wavelength is, for example, 190 nm to 10.6 μm.

[0091] In order to prevent cracks from occurring around the hole, it is preferable to use a laser processing method that minimizes the thermal effects as much as possible, and for example, a laser with a short wavelength can be used. The wavelength is, for example, 1064 nm or less, more preferably 780 nm or less, and even more preferably 532 nm or less. In addition, when using a laser with a long wavelength such as a CO2 laser, the thermal effects can be suppressed by oscillating the laser with short pulses. EXAMPLES

[0092] Next, the present invention will be further described with reference to the following Experimental Examples. In the following Experimental Examples, glasses having the compositions shown in Tables 1 and 2 were used. Note that Experimental Examples 1 to 47 are all examples of the present invention.

[0093] [Table 1]

[0094] [Table 2]

[0095] Next, details of each experimental example will be described. The experimental conditions and results of the experimental examples are summarized in the following Tables 3 to 6 and Figures 1 to 3.

[0096] (Experimental Example 1) Glass raw materials were mixed to obtain the glass composition shown in Table 1, and weighed out to obtain 500 g of glass. The mixed glass raw materials were then placed in a platinum crucible and placed in an electric furnace at 1600°C to melt for about 3 hours, degassed, and homogenized. The resulting molten glass was poured into a metal mold (e.g., a SUS surface plate) at room temperature, and the metal mold was placed in the furnace and held at the glass transition temperature for 3 hours, and then cooled to room temperature at a rate of 0.5°C / min to obtain an amorphous glass block.

[0097] Next, the obtained amorphous glass block was processed into a rectangular parallelepiped with a length of 30.0 mm, a width of 30.0 mm, and a thickness of 2.0 mm, and the 30.0 mm x 30.0 mm surface was polished to a mirror surface. The processed amorphous glass was placed in a furnace, heated to 720°C at a rate of 5°C / min, heated at 720°C for 6 hours, and then cooled to room temperature at a rate of 5°C / min to obtain crystallized glass. The physical properties of the obtained crystallized glass were evaluated by the following method.

[0098] (Measurement of dielectric properties of amorphous glass and glass-ceramic) The amorphous glass and crystallized glass obtained were processed into a rectangular parallelepiped with a length of 30.0 mm, a width of 30.0 mm, and a thickness of 0.5 mm, and the 30.0 mm × 30.0 mm surface was polished to a mirror finish. The relative dielectric constant εr and the dielectric loss tangent tanδ at 10 GHz were measured by the slip post dielectric resonance method (SPDR method) using a network analyzer.

[0099] (Measurement of crystallinity, crystallite size, and distortion of glass-ceramics) The crystallized glass obtained was subjected to PXRD measurement according to the following procedure to identify the crystal species. Then, Rietveld analysis was performed to calculate the crystallinity, the average crystallite size in the {400}, {020} and {002} planes, and the distortion in the {400}, {020} and {002} planes.

[0100] (PXRD measurement sample preparation conditions) The crystallized glass subjected to the SPDR method was pulverized using an agate mortar and an agate pestle to obtain a powder for PXRD measurement.

[0101] (PXRD measurement conditions) The obtained powder for PXRD measurement was subjected to powder X-ray diffraction under the following conditions to identify the precipitated crystals. The crystal species were identified using diffraction peak patterns recorded in the ICSD inorganic crystal structure database and the ICDD powder diffraction database. Measurement equipment: Rigaku SmartLab Measurement method: Concentration method Tube voltage: 45kV Tube current: 200mA X-ray used: CuKα ray Measurement range: 2θ=10°~80° Speed: 10° / min Step: 0.02°

[0102] (Rietveld analysis measurement sample preparation conditions) The crystallized glass powder used in the PXRD measurement (powder for PXRD measurement) was passed through a 500 μm mesh, and then 10 wt % of ZnO was added as a standard substance to obtain a powder for Rietveld analysis measurement.

[0103] (Rietveld analysis conditions) The obtained powder for Rietveld analysis was subjected to powder X-ray diffraction under the following conditions, and the obtained results were used to perform Rietveld analysis. Measurement equipment: Rigaku SmartLab Measurement method: Concentration method Tube voltage: 45kV Tube current: 200mA X-ray used: CuKα ray Measurement range: 2θ=10°~90° Speed: 5° / min Step: 0.01°

[0104] The powder X-ray diffraction profile obtained under the above conditions was analyzed using the Rietveld analysis program: Rietan FP. The analysis of each sample was converged so that Rwp, which indicates the quality of convergence of the analysis, was 10 or less. The Rietveld method is described in "Crystal Analysis Handbook" edited by the Editorial Committee of the Crystallographic Society of Japan (Kyoritsu Shuppan, 1999, pp. 492-499).

[0105] (Calculation of crystallinity) The weight ratios of the crystal phase and the remaining glass phase obtained by Rietveld analysis were calculated so that the added 10 wt% of ZnO was subtracted and the remaining phases totaled 100 wt%.

[0106] (Calculation of crystallite size) BaSi2O5 and Ba2Si4O obtained by Rietveld refinement 10 2θ, full width at half maximum (FWHM): β, and wavelength λ of Cu-Kα line used for measurement Cu-Kα The crystallite size was calculated from the Scherrer formula using the formula: 1.540593 Å, with the Scherrer constant K being 0.9. Crystallite size = K × λ Cu-Kα / (β × cosθ)

[0107] (Distortion calculation) The skewness: Dd / d obtained by Rietveld analysis was used.

[0108] (Experimental Examples 2 to 22) In Experimental Examples 2 to 22, amorphous glass was formed using the same composition and method as in Experimental Example 1, and crystallization was performed by changing the heat treatment method. Changes in the heat treatment method from Experimental Example 1 and the experimental results are shown in Tables 3 to 6 below.

[0109] [Table 3]

[0110] [Table 4]

[0111] [Table 5]

[0112] [Table 6]

[0113] (Examples 23-47) In Experimental Examples 23 to 47, the glass material and the heat treatment method were changed. The changes from Experimental Example 1 and the results are summarized in Tables 7 to 10.

[0114] In Experimental Examples 23 to 36, the amount of Li2O added to the glass was changed within the range of 0 to 5 mol %, and the heat treatment conditions were also changed.

[0115] In Experimental Examples 37-46, the additive composition was changed. In Experimental Examples 37-39, the amount of Na2O added was changed in the range of 0-2 mol%, and in Experimental Examples 40-43, the amounts of k2O, ZrO2, and TiO2 added were changed, and the heat treatment conditions were also changed. In Experimental Examples 44-46, the amounts of Al2O3 and Li2O added, and the heat treatment conditions were changed. The conditions and results of the above experiments are summarized in Tables 7 to 10 below.

[0116] [Table 7]

[0117] [Table 8]

[0118] [Table 9]

[0119] [Table 10]

[0120] Figure 1 shows BaSi2O5 and Ba2Si4O 10 The relationship between the total crystallinity and the dielectric tangent tanδ is plotted. 10 In order to examine the effect of the degree of crystallinity, the samples of composition H in which Li-based crystals were generated (Examples 32 to 36) were excluded. 10 The total crystallinity of the samples was 15 to 50 wt %, and the dielectric loss tangent tan δ was 0.030 or less. Furthermore, in samples with a crystallinity of 31% or less, the dielectric loss tangent tan δ was 0.010 or less.

[0121] In addition, in some of the experimental examples 32 to 36 using composition H containing 5 mol% Li2O, Li-based crystals Li2Si2O5 were precipitated. Figure 2 plots the relationship between the crystallinity of Li2Si2O5 in composition H and the dielectric loss tangent tanδ. As shown in Figure 2, it can be seen that as the Li2Si2O5 crystals increase, the dielectric loss tangent tanδ tends to increase. For example, the samples in which Li2Si2O5 crystals precipitated were similarly enriched in BaSi2O5 and Ba2Si4O. 10The dielectric loss tangent tanδ was higher than that of other samples in which Li-based crystals were not precipitated. Therefore, when Li2O is added, it is preferable to carry out a crystallization process so that Li-based crystals are not precipitated.

[0122] In FIG. 3, the relationship between the sum of squares of the difference in lattice constants of the above-mentioned index 1 and the dielectric loss tangent tanδ is plotted. In order to exclude the influence of the Li-based crystals, the results of the samples of composition H (Experimental Examples 32 to 36) are not plotted. Also, the straight line in FIG. 3 shows an approximation line for the samples of composition F. From FIG. 3, it can be seen that when the sum of squares of the difference in lattice constants decreases, the distortion of the crystal can be suppressed and the dielectric loss tangent tanδ can be reduced. In particular, when the sum of squares of the difference in lattice constants is 0.025 or less, the dielectric loss tangent tanδ is 0.0010 or less. Also, it can be seen that in composition F, the sum of squares of the difference in lattice constants and the dielectric loss tangent tanδ are in a linear relationship. Therefore, in the sample using composition F, BaSi2O5 and Ba2Si4O 10 It is believed that only the crystal phase of

[0123] Figure 4 shows the sum of the products of the crystallinity of BaSi2O5 and the strain on each of the {002}, {020}, and {400} planes of BaSi2O5, which is the index 2, and the strain on each of the {002}, {020}, and {400} planes of BaSi2O5, which is the index 3. 10 Crystallinity and Ba2Si4O 10 The relationship between the sum of the products of the strains in the {002}, {020}, and {400} planes (crystallinity x strain total) and the dielectric loss tangent tanδ of the crystallized glass was plotted. As shown above, it can be seen that the dielectric loss tangent tanδ can be significantly reduced by reducing the value of the sum of the crystallinity x strain, which indicates the total amount of strain in the crystallized glass. In particular, when the sum of the crystallinity x strain was 0.019 or less, the dielectric loss tangent tanδ was 0.010 or less.

[0124] 3 and 4, in Experimental Example 39 and Experimental Example 41, which used Composition K containing 2 wt% Na2O and Composition N containing 2 wt% Ti2O, the dielectric loss tangent tanδ increased with respect to the amount of measured strain. This is thought to be because Na2O and Ti2O contribute to an increase in the dielectric loss tangent of glass, and therefore the dielectric loss tangent tanδ increases.

[0125] Although the present invention has been described in detail and with reference to specific embodiments, it is apparent to those skilled in the art that various changes and modifications can be made without departing from the spirit and scope of the present invention. This application is based on a Japanese patent application (Patent Application No. 2020-060908) filed on March 30, 2020, the contents of which are incorporated herein by reference.

Claims

1. A crystallized glass having a crystalline phase consisting only of Ba--Si--O.

2. The crystalline phase is BaSi 2 O 5 and Ba 2 S 4 O 10 The crystallized glass according to claim 1 , comprising at least one of the following:

3. The BaSi 2 O 5 Crystallinity and Ba 2 S 4 O 10 3. The crystallized glass according to claim 2, wherein the total crystallinity value of the above is 15% or more and 50% or less in weight percent.

4. 4. The crystallized glass according to claim 1, wherein the crystallized glass contains Li, and the degree of crystallization of the Li-based crystals contained in the crystal phase is 20% or less in terms of weight percent.

5. 5. The crystallized glass according to claim 2, wherein the sum of squares of the differences in lattice constants represented by the following formula is 0.050 or less. (Sum of squares of lattice constant differences) = (A BS2 -A' BS2 ) 2 + (B BS2 -B' BS2 ) 2 + (C BS2 -C' BS2 ) 2 + (A B2S4 -A' B2S4 ) 2 + (B B2S4 -B' B2S4 ) 2 + (C B2S4 -C' B2S4 ) 2 Here, BaSi measured in the crystalline phase 2 O 5 The lattice constant of A BS2 , B BS2 , C BS2 And Ba 2 S 4 O 10 The lattice constant of A B2S4 , B B2S4 , C B2S4 and BaSi in an ideal crystal state as described in ICSD Collection Code: 15486. 2 O 5 The lattice constant of A' BS2 , B' BS2 , C' BS2 and Ba in an ideal crystalline state as described in ICSD Collection Code: 9339. 2 S 4 O 10 The lattice constant of A' B2S4 , B' B2S4 , C' B2S4 Let us assume that.

6. The BaSi 2 O 5 The crystallinity of BaSi 2 O 5 the sum of the products of the strains on the {400}, {020} and {002} planes of the Ba 2 S 4 O 10 The crystallinity of Ba 2 S 4 O 10 6. The crystallized glass according to claim 2, wherein the sum of the products of strain in each of the {400} plane, the {020} plane, and the {002} plane is 0.030 or less.

7. The crystallized glass according to any one of claims 1 to 6, having a composition α such that the sum of squares of the differences in lattice constants and the dielectric loss tangent at 10 GHz have a linear relationship, as determined by the following test method. Test method: (i) A plurality of amorphous glasses each having a composition α are prepared, and a plurality of samples are produced by changing the crystallization conditions. (ii) The dielectric loss tangent at 10 GHz of each of the samples is measured. (iii) In each sample, BaSi in the crystalline phase 2 O 5 Lattice constant A BS2 , B BS2 , C BS2 and Ba in the crystal phase 2 S 4 O 10 Lattice constant A B2S4 , B B2S4 , C B2S4 Measure. (iv) The sum of squares of the differences in lattice constants for each sample is calculated using the following formula: BaSi in an ideal crystalline state as described in ICSD Collection Code: 15486 2 O 5 The lattice constant of A' BS2 , B' BS2 , C' BS2 and Ba in an ideal crystalline state as described in ICSD Collection Code: 9339. 2 S 4 O 10 The lattice constant of A' B2S4 , B' B2S4 , C' B2S4 Then, (Sum of squares of lattice constant differences) = (A BS2 -A' BS2 ) 2 + (B BS2 -B' BS2 ) 2 + (C BS2 -C' BS2 ) 2 + (A B2S4 -A' B2S4 ) 2 + (B B2S4 -B' B2S4 ) 2 + (C B2S4 -C' B2S4 ) 2 (v) determining a correlation between the sum of squares of the differences in the lattice constants of the multiple samples and the dielectric loss tangents at 10 GHz of the multiple samples;

8. The crystallized glass according to claim 7, wherein the linear relationship is expressed by the following formula, using an arbitrary slope a and an intercept b, where X is the sum of squares of the differences in the lattice constants and Y is the dielectric loss tangent at 10 GHz. Y = ax + b and a>0 and b<0.0030

9. In mole percent based on oxide, Yes 2 :68~78% <h2 style=";text-align:left;direction:ltr">Al<h2 style=";text-align:left;direction:ltr"> 2 <h2 style=";text-align:left;direction:ltr"> O<h2 style=";text-align:left;direction:ltr"> 3 <h2 style=";text-align:left;direction:ltr"> :0~5% BaO: 24-35% Li 2 O:0~6% Na 2 O:0~3% K 2 O: 0~3% ZrO 2 :0~4% TO 2 :0~4% Contains (Li 2 O+Na 2 O+K 2 O): Meets 0-6%; The crystallized glass according to any one of claims 1 to 8.

10. Li 2 The crystallized glass according to any one of claims 7 to 9, having an O content of more than 0 to 5%.

11. ZrO 2 and TiO 2 The crystallized glass according to any one of claims 7 to 10, wherein the total content of is more than 0 to 5%.

12. A high frequency substrate using the crystallized glass according to any one of claims 1 to 11.

13. 13. The high frequency substrate according to claim 12, having a dielectric loss tangent of 0.0030 or less at 10 GHz.

14. 14. The high frequency substrate according to claim 12, having a relative dielectric constant of 6.0 or more and 8.0 or less at 10 GHz.

15. 15. The high frequency substrate according to claim 12, having a thickness of 0.05 mm or more and 1 mm or less.

16. It has two main surfaces facing each other, and the area of ​​the main surfaces is 75 cm 2 The high frequency substrate according to any one of claims 12 to 15, wherein:

17. 17. The high frequency substrate according to claim 12, comprising two main surfaces opposed to each other, at least one of the main surfaces being provided with a hole having an opening.

18. BaO and SiO 2 A raw material containing the compound is melted and molded to obtain an amorphous glass, The amorphous glass is crystallized by maintaining the amorphous glass at a treatment temperature of 600° C. or more and less than 1000° C. A method for producing crystallized glass having a crystal phase consisting only of Ba--Si--O.

19. The method of claim 18, wherein the amorphous glass is maintained at the treatment temperature for at least 0.5 hours.

20. The method according to claim 18 or 19, wherein the treatment temperature is equal to or higher than a glass transition point Tg of the amorphous glass measured by a differential scanning calorimeter (DSC).

21. 21. The method of claim 18, wherein the crystallization of the amorphous glass comprises a two-stage heat treatment in which the amorphous glass is held at a first treatment temperature and then held at a second treatment temperature higher than the first treatment temperature.

22. The method according to claim 21, wherein the first treatment temperature is equal to or higher than a glass transition temperature Tg and equal to or lower than a crystallization onset temperature Tx of the amorphous glass measured by a differential scanning calorimeter (DSC).

23. The method according to claim 21 or 22, wherein the second treatment temperature is equal to or higher than a crystallization onset temperature Tx of the amorphous glass measured by a differential scanning calorimeter (DSC).

Citation Information

Patent Citations

  • Electron device

    JP2004345950A

  • Thin, fine-grained, and fully dense glass-ceramic seals for SOFC stacks

    JP2013516378A

  • Barium silicate glass-ceramic body and method of making it

    US3467534A